Sebaran dan Keparahan Penyakit Gugur Daun pada Tanaman Karet - Rifa'i, Muhammad; Budi, Ismed Setya; Mariana, Mariana (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
In recent years, the rubber industry in Indonesia has experienced problems because rubber plants have been attacked by leaf fall disease which can reduce latex production by up to 50% and even cause them to wilt and die. In 2021, leaf fall disease began to be detected attacking rubber plantations in South Kalimantan, but it has not been reported on rubber plantations in Barito Kuala. This research aims to determine the distribution of rubber leaf fall disease on rubber plants in Barito Kuala Regency. The method used is a survey method, sampling was carried out using stratified purposive random sampling and creating a questionnaire as supporting data. The survey was conducted in Barito Kuala Regency in four selected rubber growing center sub-districts, namely Wanaraya, Barambai, Marabahan and Anjir Pasar sub-districts, three villages were selected in each sub-district. Each village was sampled diagonally with 25 trees at each sample point so that there were 125 trees per village with a total sample area of ​​12 villages. So in four sub-districts there were 1,500 trees observed. The parameters observed were the incidence and severity of rubber leaf fall disease. The severity of rubber leaf fall disease in Barito Kuala Regency is quite severe with an average of 65%. The level of severity in each location varies, starting from 48% in Gandaria Village, Anjir Pasar District, to 82% in Kolam Kiri Dalam Village, Barambai District. In Barambai District the average disease severity level is 70%, in Wanaraya District it is also almost the same, namely 71%. In Marabahan District it is lower, namely 66%. The lowest sub-district is Anjir Pasar Sub-district which only has 52%.